2017
DOI: 10.17221/364/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Toxic elements and energy accumulation in topsoil and plants of spruce ecosystems

Abstract: The objective of this research was to evaluate trends and relationships of energy and toxic elements accumulation in A-horizon (the depth of 0–5 cm) of soils and in selected plants of the hemioligotrophic (Dystric Cambisols) and oligotrophic (Skeletic-Rustic Podzols) spruce ecosystems situated along transect (750–1110 m a.s.l.) in the NP Slovenský raj (Eastern Slovakia). The results showed that EU limit values of risk elements in agricultural soils were exceeded for Cu and Cd at the altitude of 750–760 m a.s.l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The aim of this study was to determine the content of heavy metals in two plant species depending on the absolute altitude in mountain areas. This relationship was observed in world studies of various components of the environment (soil, plants) and mountain ranges [29][30][31][32][33][34][35]. The mentioned authors observed an increase in the content of metals in plants with increasing altitude.…”
supporting
confidence: 52%
“…The aim of this study was to determine the content of heavy metals in two plant species depending on the absolute altitude in mountain areas. This relationship was observed in world studies of various components of the environment (soil, plants) and mountain ranges [29][30][31][32][33][34][35]. The mentioned authors observed an increase in the content of metals in plants with increasing altitude.…”
supporting
confidence: 52%
“…Agricultural crops show varied levels of sensitivity to the given metal; with majority of them accumulating Cd in roots (Vamerali et al, 2012, Wu 1990). In plants, exposure to Cd causes oxidative stress, inhibition of growth, nutritional imbalances, changes in the activity of many enzymes, reduction of a transpiration rate and water content (Barceló and Poschenrieder, 1988;Benavides et al, 2005;Kuklová et al, 2017). In addition, it causes stomatal closure due to entry of Cd into the guard cells in competition to Ca +2 (Perfus-Barbeoch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the stomatal density, size of stomata and epidermal cells as a response to environmental stress are important means of regulating the rate of absorption of risk elements by plants, while the stomatal index often remains unchanged (Gostin, 2009). Several authors suggest that leaves of resistant species show xeromorph characteristics, which most probably help plants adapt to the increased concentrations of heavy metals and gases (Kutschera-Mitter et al, 1982;Nikolaevkij, 1989). Many studies have attempted to clarify the mechanism of heavy metal toxicity in plants (Benavides et al, 2005;Procházková et al, 2014;Kohanová et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the author of the present study, an increase in the content of metals in plants along with an increase in altitude was found in their research by Shetekauri et al [35] in the western Caucasus Mountains for As, Cd, Ti, W in mosses, Sahin et al [36] in the Kumalar Mountains for Cu, Zn in herbaceous plants, Zechmeister [32] in the Alps for As, Pb, Zn, and V in the P. schreberi and Hylocomium splendens, Šoltés [37] for the content of Pb in the Sphagnum girgensohnii in the Tatra Mountains in Slovakia, Samecka-Cymerman et al [38] in the Tatra National Park for the content of Cd, Ni, and Zn in the Athyrium distentifoliu, Panek [39] in the Poland's Carpathian region for Pb in P. formosum and Kuklová et al [40]. Kuklová et al [40] found an increase in the content of Cu and Zn in three plant species (the Dryopteris filix-mas, Rubus idaeus, and V. myrtillus) with an increase in altitude. They observed an increase in the Cd content for two plant species: the D. filix-mas and the V. myrtillus.…”
Section: Discussionmentioning
confidence: 99%